Development of a model for integration of assembly and disassembly in life cycle management - Memary, Reza (2009)
Regarding the high rate of scrap increase in developed and developing countries, governments and unions are issuing legislations to force companies recycling their products after disposal all over the world. This fact is obvious in vehicle and electrical appliances industry. Currently at the end of life of products recyclers think how to take advantage of product end of life. This problem originates from product design and development process. In order to achieve environmentally conscious products, these two elements have to be considered i.e. assembly and disassembly. Consequently, new approaches in design such as design for disassembly are introduced. Through these new approaches, companies are able to take benefit of their product end of life value. But still there is some vague area in design for environment especially when designer wants to combine all aspects at the early stage of design. Tools which are able to consider all design aspects concurrently will decrease total cost in product life cycle and will motivate producers not only to follow legislations, but also get higher benefit of product end of life. This research expects finding methodologies that can combine assembly and disassembly for a less life cycle cost.